Assessing Employability Skills of Technical-Vocational Students in Malaysia - Bakar, Ab. Rahim; Hanafi, Ivan (Science Publications, 2007)
Technical-Vocational Education and Training (TVE) system plays important role in providing highly skilled workforce to fulfill the needs of industries. An empirical research of TVE system is necessary to identify effective TVE system to successfully equip students with technical skills that would enable them to fulfill the current work demands and professional expectations. The objective of this paper is to present the findings of TVE system implementation in one of the technical training institution in Malaysia. Research sample has been selected using a simple random method from the third year students. A total of 162 students participated in this research. The result shows that mean score for overall employability skills was quite high. Two aspects of the employability skills, namely, thinking skills and resource management competence and system & technology competence were slightly lower than the mean score. Respondents have slightly higher than the mean scores on basic informational competence interpersonal competence. The mean score of personal quality is the highest among all the aspects of variables of employability skills.